Novel flux-switching machine with star-array permanent-magnet arrangement - Shen, Fawen (2022)
This paper presents a novel flux-switching (FS) machine adopting star-array permanent-magnets (PMs), termed as star-FSPM machine. In comparison with the conventional spoke-FSPM machine, the proposed one can achieve not only enhanced flux-concentration effect but also enlarged stator-slot area, thus improving PM utilization ratio and torque density. The harmonic characteristics of both PM field and armature reaction field in the star-FSPM machine are investigated based on the field modulation theory. More importantly, the torque generation mechanism of the star-FSPM machine is also investigated and compared with that of the spoke-FSPM machine. The results show that the proposed machine can utilize the working harmonics more effectively for torque generation. Afterwards, the electromagnetic performance comparison of four PM machines is carried out by finite element analysis (FEA). It is found that the proposed star-FSPM machine exhibits improved PM utilization ratio and enhanced torque density as compared to the spoke-FSPM machine. Finally, the theoretical analysis and FEA results are verified by experimental measurement.